Le nuove sfide della genitorialità: il caso dell’omogenitorialità e il ruolo della Costituzione (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper analyses the juridical condition of homoparentality in Italy. The paper focuses on the role played by the Constitution in the recognition of a legal protection, facing the silence of the Law no. 76 of 2016 on civil unions. By framing these issues, the paper addresses the following questions. May we consider parentality as a “right” or is there a right to protect the family as a «natural society based on marriage» (article 29 of the Italian Constitution)? How does the public order play in the (non) protection of same-sex parentality? Which are the risks and the possibility in the use of Constitution in front of the silent Parliament?
Keywords: Homoparentality; case-law; constitutional protection; self-determination; parental rights